How are clinical exercise physiology postgraduate courses taught and assessed in the UK? A multimethod qualitative exploration - Helen Jones; Daniel J Green; Louise H Naylor; Lee Graves; Gemma Miller; Anthony Crozier; Christopher David Askew; Ellen A Dawson; Connor Osin; Ian Sadler (BMJ Open)
Introduction Development of clinical skills in areas, such as exercise risk stratification, testing, prescription, monitoring and outcome assessment, is vital for patient safety and clinical effectiveness in clinical exercise physiology (CEP). This study explored how current CEP courses are being taught and assessed and to identify potential best practice recommendations from a variety of stakeholdersMethods Qualitative methods were employed to explore the thoughts of CEPs, academics and current students regarding the teaching and assessment of CEPs in the UK. Research design involved (1) semistructured interviews with students (n=16) and (2) focus groups with academics (n=8) and CEP (n=5) stakeholders. Data obtained were audio recorded using a portable Dictaphone and transcribed verbatim, then thematically analysed manually.Results Three themes: (1) in situ learning/real-world practice (working with patients and specialist practitioners); (2) programme design (scaffold learning and integrated modules) and (3) teaching approach (simulated learning and research competency) were generated concerning teaching methods and approaches across CEP postgraduate degrees. The current use of simulated tasks for the delivery of taught content was identified as lacking effectiveness, with clinical placements identified as being the most important source of knowledge and skill attainment due to the real-world exposure to patients and practitioners. Clinical placements and simulated learning were recognised as the two main methods of problem-based learning used to develop student knowledge, skills and competency to practice. Two themes (placement tariffs/assessors in situ and role play/simulation) were identified for the assessment of students.Conclusion Clinical placements remain the optimal method for developing the knowledge, skills and competency to practice for student CEPs. However, suitable placements remain limited, and novel approaches such as university-led exercise services require consideration for student competency development. A standardised and accredited training pathway from undergraduate through to postgraduate level should be explored to allow student competency to be developed over a longer period, to enhance knowledge, skills and competency on graduation and registration.